Pengaruh Sedimentasi Terhadap Kapasitas Aliran Sungai Menggunakan Metode Frijlink Dan Pemodelan HEC-RAS - Parta Wijaya; Sartika Nisumanti; Ratih Baniva (Jurnal Konstruksi, 2026)
Sedimentation is one of the main factors affecting the hydraulic capacity and performance of urban rivers. This study aims to analyze flow capacity and the impact of sedimentation on a river’s ability to convey flow optimally. Flow capacity analysis was conducted using the Frijlink method with a rectangular channel cross-section approach, while sediment distribution and accumulation were analyzed through hydraulic modeling using HEC-RAS software. The analysis results show that the river’s flow capacity is 3,381 m3/s. An evaluation of bed sedimentation indicates that observation point 3 has the highest sedimentation rate, with a sediment discharge of 2.85 × 10-8 m3/s/m and a sedimentation volume of 5.78 × 10-4 m3/s. The HEC-RAS modeling results show that the river’s capacity is unable to accommodate the flow rate optimally under high rainfall conditions, thus potentially causing local flooding or waterlogging.